2004
DOI: 10.1158/0008-5472.can-04-0757
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Granulocyte-Macrophage Colony-Stimulating Factor-Producing Vaccines Impair the Immune Response through the Recruitment of Myeloid Suppressor Cells

Abstract: Tumor vaccines have shown promise in early clinical trials. Among them, tumor cells genetically engineered to secrete biologically active granulocyte-macrophage colony-stimulating factor (GM-CSF) can generate a systemic antitumor immune response. Although the minimal required GM-CSF dose produced by modified tumor cells to achieve a measurable antitumor effect is well known, no data examined whether an upper therapeutic limit may exist for this vaccination strategy. Because recent data demonstrate an immunosup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
360
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(385 citation statements)
references
References 38 publications
22
360
1
Order By: Relevance
“…Such immunosuppression has been demonstrated in animal studies using high GM-CSF-secreting cellular vaccines. 21 However, the serum GM-CSF levels measured in patients in this study were consistently below the levels associated with immunosuppression in animals (4250 pg/ml) and, generally, were in the range associated with a therapeutic vaccine effect (p40 pg/ml), making this explanation unlikely.…”
Section: Discussionmentioning
confidence: 48%
“…Such immunosuppression has been demonstrated in animal studies using high GM-CSF-secreting cellular vaccines. 21 However, the serum GM-CSF levels measured in patients in this study were consistently below the levels associated with immunosuppression in animals (4250 pg/ml) and, generally, were in the range associated with a therapeutic vaccine effect (p40 pg/ml), making this explanation unlikely.…”
Section: Discussionmentioning
confidence: 48%
“…While physiological concentrations of GM-CSF are required for normal myelopoiesis, chronic administration of GM-CSF resulted in the generation of immune suppressive Gr-1 + CD11b + cells in mice [184]. Experimental tumors overexpressing GM-CSF induced a systemic increase of immature myeloid cells, which was associated with suppression of T cell immune responses [184][185][186]. However, irradiated cancer cells engineered to secrete GM-CSF elicited potent anti-tumor immune responses in various animal tumor models [187].…”
Section: Regulation Of Neutrophil Mobilization Recruitment and Activmentioning
confidence: 99%
“…We found that stimulation of TLR7 expressed by adenocarcinoma cells modulated the immune infiltrate, leading to a significant expansion in MDSCs, associated with an increased secretion of CCL2 and GM-CSF in the tumor microenvironment. Both these cytokines are known to play a key role in the recruitment of MDSCs 38,41,42 . Indeed, the absence of CCL2 production by cancer cells considerably reduces the recruitment of MDSCs into tumors 42 .…”
Section: Discussionmentioning
confidence: 99%